Impaired B Cell Function in Mice Lacking Perforin-2 - Frasca, Daniela; Diaz, Alain; Romero, Maria; Vazquez, Thomas; Strbo, Natasa; Romero, Laura; McCormack, Ryan M.; Podack, Eckhard R.; Blomberg, Bonnie B. (Frontiers in Immunology, 2020)
Perforin-2 (P2) is a pore-forming protein with cytotoxic activity against intracellular bacterial pathogens. P2 knockout (P2KO) mice are unable to control infections and die from normally non-lethal bacterial infections. Here we show that P2KO mice as compared to WT mice show significantly higher levels of systemic inflammation, measured by inflammatory markers in serum, due to continuous microbial translocation from the gut which cannot be controlled as these mice lack P2. Systemic inflammation in young and old P2KO mice induces intrinsic B cell inflammation. Systemic and B cell intrinsic inflammation are negatively associated with in vivo and in vitro antibody responses. Chronic inflammation leads to class switch recombination defects, which are at least in part responsible for the reduced in vivo and in vitro antibody responses in young and old P2KO versus WT mice. These defects include the reduced expression of activation-induced cytidine deaminase (AID), the enzyme for class switch recombination, somatic hypermutation and IgG production and of its transcriptional activators E47 and Pax5. Of note, the response of young P2KO mice is not different from the one observed in old WT mice, suggesting that the chronic inflammatory status of mice lacking P2 may accelerate, or be equivalent, to that seen in old mice. The inflammatory status of the splenic B cells is associated with increased frequencies and numbers of the pro-inflammatory B cell subset called Age-associated B Cells (ABCs) in the spleen and the visceral adipose tissue (VAT) of P2KO old mice. We show that B cells differentiate into ABCs in the VAT following interaction with the adipocytes and their products, and this occurs more in the VAT of P2KO mice as compared to WT controls. This is to our knowledge the first study on B cell function and antibody responses in mice lacking P2.